2021
DOI: 10.1016/j.ajo.2020.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Key Retinal Features in Early and Late Age-Related Macular Degeneration Using Deep Learning

Abstract: We sought to develop and validate a deep learning model for segmentation of 13 features associated with neovascular and atrophic age-related macular degeneration (AMD).DESIGN: Development and validation of a deeplearning model for feature segmentation.METHODS: Data for model development were obtained from 307 optical coherence tomography volumes. Eight experienced graders manually delineated all abnormalities in 2712 B-scans. A deep neural network was trained with these data to perform voxel-level segmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…In this context, previous studies reported on machine and deep learning (DL)–based methods in eyes with early and intermediate AMD to reliably detect structural biomarkers as lesions of hyperreflective foci (HRF) and RPD, to quantify drusen volumes, and to estimate the individual's eye risk toward disease progression. 27 29 In another study, Liefers et al 30 even revealed findings on DL-based models exceeding the human performance on the detection of neovascular AMD-associated structural biomarkers. Interestingly, in the same data set, the accuracy rate for detecting drusen and drusenoid PEDs was slightly higher for readers than for the model.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this context, previous studies reported on machine and deep learning (DL)–based methods in eyes with early and intermediate AMD to reliably detect structural biomarkers as lesions of hyperreflective foci (HRF) and RPD, to quantify drusen volumes, and to estimate the individual's eye risk toward disease progression. 27 29 In another study, Liefers et al 30 even revealed findings on DL-based models exceeding the human performance on the detection of neovascular AMD-associated structural biomarkers. Interestingly, in the same data set, the accuracy rate for detecting drusen and drusenoid PEDs was slightly higher for readers than for the model.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, in the same data set, the accuracy rate for detecting drusen and drusenoid PEDs was slightly higher for readers than for the model. 30 However, further studies validating machine learning approaches to differentiate disease phenotypes in multimodal retinal imaging as well as to detect early signs for disease progression as, for example, lesions of iRORA in eyes with iAMD are currently still ongoing. The availability of standardized gradings on various structural biomarkers as well as multimodal retinal imaging data within the MACUSTAR study can form the basis for the development of further automated grading approaches, which will also help to grade the increasing amount of multimodal retinal imaging data sets available in currently ongoing and future multicenter, observational clinical iAMD trials.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 18 , 19 However, because the calculation for DSC is highly dependent on the area of interest, 15 , 16 it becomes more difficult to achieve higher DSCs on smaller structures such as the retina. As examples, Deeley et al 20 reported average DSCs of 0.4 to 0.5 when segmenting nerves and the optic chiasm on brain magnetic resonance imaging (MRI) scans, whereas Liefers et al 21 reported a mean DSC of 0.6 when developing an algorithm to segment features of age-related macular degeneration on OCT. Additionally, our segmentation was more challenging as the leakage boundary was more ambiguous compared to boundaries for other forms of imaging.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…However, we do note that even between expert human graders, we measured considerable, and higher, inter-rater reliability. Others have also observed intra-grader variability in FA 1 and more easily interpretable images such as OCT. 21 This discordance between clinicians could have serious impacts on patient care, and thus a more objective tool to evaluate FAs has great clinical importance.…”
Section: Conclusion/discussionmentioning
confidence: 99%
“…This methodology has been applied to investigating imaging biomarkers and visual outcomes [ 24 ▪ , 26 ▪▪ ]. Following this, another group developed a novel automated segmentation model using a convolutional neural network [ 27 ▪ ]. This model was built using a large, real-world electronic medical records-based dataset from the United Kingdom, annotated by clinical experts with 13 of the most common AMD biomarkers on OCT, including IRF, SRF, and pigment epithelial detachment (PED) [ 27 ▪ ].…”
Section: Development and Application Of Artificial Intelligence Models For Neovascular Age-related Macular Degenerationmentioning
confidence: 99%